Experimental evidence on the long term impacts of a youth training program - Pablo Ibarrarán; Jochen Kluve; Laura Ripani; David Rosas Shady (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
This paper presents the results of a randomized controlled trial on the long-term impacts of a youth training program. The empirical analysis estimates labor market impacts six years after the training - including long-term labor market trajectories of young people - and, to the best of our knowledge, is the first experimental long-term evaluation of a youth training program outside the US. We are able to track a representative sample of more than 3,200 youths at the six-year follow-up. Our empirical findings document significant impacts on the formality of employment, particularly for men, and impacts for both men and women in Santo Domingo, the capital of the Dominican Republic. The long-term analysis shows that these impacts are sustained and growing over time. There are no impacts on average employment, which is consistent with the low unemployment in countries with high informality and no unemployment insurance. Looking at the local labor market context, the analysis suggests that skills training programs work particularly well in more dynamic local contexts, where there is actual demand for the skills provided. – – Dieses Papier untersucht die langfristigen Arbeitsmarkteffekte einer Bildungsmaßnahme für benachteiligte Jugendliche und junge Erwachsene in der Dominikanischen Republik. Die empirische Analyse basiert auf einer randomisierten Zuordnung von teilnahmeberechtigten Personen in eine Teilnahme- und Kontrollgruppe, und ist unseres Wissens nach die erste experimentelle Langzeitstudie einer solchen Maßnahme außerhalb der USA. Die Stichprobe enthält Daten zu mehr als 3200 Personen sechs Jahre nach der Zuweisung in Teilnahme- und Kontrollgruppe. Die Ergebnisse zeigen signifikant positive Effekte auf formale Beschäftigung, insbesondere für Männer, sowie auf Arbeitseinkommen für Frauen. Die positiven Wirkungen zeigen sich insbesondere für Personen in der Hauptstadt Santo Domingo, dem dynamischsten lokalen Arbeitsmarkt des Landes, in dem reale Nachfrage für die in der Maßnahme erworbenen Fähigkeiten besteht.
Keywords: J24; J64; O15; O17; 330; long-term; impact evaluation; Randomized Controlled Trial; Dominican Republic; youth training; labor market outcomes